Chromatogram and Spectram Profiles Antimalarial Isolate from Dichloromethane Extract of Artocarpus champeden Spreng. Stem Bark - Nuri Nuri (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2007)
The isolate which possessed antimalarial activity had been isolated from dichloromethane extract of Artocarpus champeden Spreng. Stem bark. The isolate inhibited Plasmodium falciparum growth in vitro by IC 0.024±0.011 μg/ml. Chromatogram and spectram of isolate analysis showed that it contained flavonol as a major compound.